Analisis Implementasi Program Perlindungan Anak Terpadu Berbasis Masyarakat (PATBM): Studi Kasus di Kabupaten Majalengka - Jayanti, Wida Putri Dwi; Muliawaty, Lia; Nasuha, Cecep Nana (IAI Nasional Laa Roiba Bogor, 2025)
This study aims to analyze and identify the implementation of the Community-Based Integrated Child Protection Program (PATBM) in Majalengka Regency, specifically in relation to the roles of the Social Service (Dinsos) and the Women's Empowerment, Child Protection, and Family Planning Service (DP3AKB). Using a qualitative-descriptive approach with a case study methodology, this study analyzes data and literature within the theoretical framework of public policy implementation by George C. Edwards III. The results indicate that the implementation of PATBM in Majalengka Regency has strong political commitment from regional leaders and effective cross-agency collaboration is a key strength. Significant challenges arise from fragmented communication channels between Dinsos and DP3AKB and an imbalance in resource allocation, which tends to focus more on post-incident case handling (responsive) than on preventative efforts (preventive). Positive stakeholder dispositions act as catalysts, enabling strong functional collaboration. Strategic steps are still needed to integrate and balance all program elements, particularly in the aspects of communication and resource allocation, to achieve comprehensive and sustainable child protection.